(untitled) (Revista de Ciências Agroveterinárias, 2006)
The potential of medicinal use of plant species from Amazon region is little explored. Several species are already, at least partly, known by the science and used in the production of medicines or industries of perfumeries. In the regional trade, markets and fairs barks, leaves, roots are marketed, the ones that the faith and the popular experience consecrated along the years and that comes provoking interest in international pharmaceutical industries. All the native species of medicinal use of amazon forest are explored through extraction, without the replacement concern, without management and without any orientation in the rational exploration. As they are, largely, arboreal species, the time to begin the production of seeds or to be explored the barks, the oil or other products, is relatively large, what doesn’t stimulate the managers to invest in the commercial exploration of long period of these species. Besides the extraction, other difficulty in the rational exploration is the lack of basic studies about the species, as phenology, production and the storage of seeds, production of young plants, plague and diseases, the handling of the plants in single cultivation or in consortium with few species. Also lacks studies on their, cultivation collects, processing, and as to join value to the products of the Amazon flora.